Efficient rendezvous schemes for fast‐varying cognitive radio ad hoc networks. Issue 12 (8th August 2017) - Al‐Mqdashi, Abdulmajid; Sali, A.; Abdel‐Rahman, Mohammad J.; Noordin, Nor Kamariah; Hashim, Shaiful J.; Nordin, Rosdiadee
Abstract: Rendezvous is a fundamental operation for establishing communications between cognitive radios in a cognitive radio ad hoc network (CRAHN). Channel hopping (CH) provides an effective method for achieving rendezvous without relying on a dedicated common control channel. Most of the existing CH‐based rendezvous schemes were not designed for CRAHNs operating under fast primary user (PU) dynamics and result in excessive rendezvous delay when applied in such dynamic environments. To cope with fast PU dynamics, we propose in this paper two efficient cyclic‐quorum–based CH rendezvous schemes, which we refer to as nested cyclic quorum channel hopping (NCQ‐CH) and minimal nested cyclic quorum channel hopping (MNCQ‐CH). The proposed schemes are tailored for the spectrum‐heterogeneous CRAHNs. In addition to proactively accounting for PU dynamics, our CH‐based rendezvous schemes are designed to react to fast PU dynamics on the fly. To achieve this online adaptation, we augment NCQ‐CH and MNCQ‐CH with efficient mechanisms for channel ranking and quorum selection. Our simulations demonstrate the superior performance of the proposed schemes under fast PU dynamics, in terms of the time‐to‐rendezvous and PU detection accuracy, as compared with existing rendezvous schemes in the literature. Abstract : In this paper, we propose two efficient cyclic‐quorum‐based CH rendezvous schemes, which we refer to as NCQ‐CH and MNCQ‐CH. These schemes are designed to account for the fast PU dynamics and the related channel variations in CRAHNs. Furthermore, our schemes are adapted to react to fast PU dynamics on the fly using efficient mechanisms for channel ranking and cyclic quorum selection. The simulations results demonstrate the superior performance of the proposed schemes under fast PU dynamics, in terms of the time‐to‐rendezvous and PU detection accuracy, as compared to existing rendezvous schemes in the literature.